The Role of Santri Organization in Guiding the Discipline of Hidayatul Insan Fii Ta'limiddin Islamic Boarding School Palangka Raya - Meilinda, Fitria; Ajahari, Ajahari; Lutfi, Saiful (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This research is motivated by the understanding that students in boarding schools must have a good attitude of discipline, in fact in boarding schools there are still many students who are punished for violating boarding school regulations. The formulation of the problem of this research is how the role of the organization in fostering the discipline of class VIII female santri MTs Hidayatul Insan Palangka Raya and what are the supporting and inhibiting factors in fostering discipline in class VIII female santri MTs Hidayatul Insan Palangka Raya. This research method uses descriptive qualitative method, with the research location at Hidayatul Insan Fii Ta'limiddin Boarding School Palangka Raya. The results showed that the role of the organization's management in providing discipline to the 8th grade boarding students is by giving a warning first to the students who first violate the rules. If the santriwati violates again, a different form of discipline is given than before. Supporting factors in fostering discipline are self-awareness of the importance of discipline by following the rules in the Pondok. While the inhibiting factor of fostering discipline is the lack of self-awareness to obey the rules.